Textual Discourse Analysis of Song Lyrics “Di Balik Rindu Ada Dusta (Natalia)” By Obbie Messakh - Setyawan, Arief; Setiawan, Budhi (UIR Press, 2024)
The song Di Balik Rindu Ada Dusta (Natalia) by Obbie Messakh is one of the popular pop songs in the 80s era. This song is about a couple who are faced with problems by the presence of a third person between them and is revealed one night when they are both in place. The purpose of this study is to examine and describe the textual aspects of the linguistic aspect of the song's lyrics. The textual aspect includes the integration of song lyrics in terms of grammatical cohesion and lexical cohesion used by the creator. This study used descriptive qualitative method. The source of the research data is the lyrics of the song (word structure) Di Balik Rindu Ada Dusta (Natalia) by Obbie Messakh. The sampling technique used was purposive sampling technique because the data were taken from a collection of songs by Obbie Messakh which were adapted to the research objectives. The data collection technique uses content analysis techniques to see the textual aspects consisting of grammatical and lexical. Based on the analysis of research data from the song’s lyrics of Di Balik Rindu Ada Dusta (Natalia) by Obbie Messakh, it can be said that there are some aspects that are included in the study of the text, namely grammatical aspects and lexical aspects. In the grammatical aspect, there are forms of (1) references (references) which include personal references, demonstrative references, and comparative references; (2) obliteration (ellipsis); and (3) substitution (substitution). From the lexical aspect, it can be found the forms of (1) repetition (repetition) which includes sequence and lexical number of syllables, and (2) synonymy (word equivalent).